EEG evidence for enhanced attentional performance during moderate‐intensity exercise. (9th August 2021) - Dodwell, Gordon; Liesefeld, Heinrich R.; Conci, Markus; Müller, Hermann J.; Töllner, Thomas
Abstract: Research on attentional control within real‐world contexts has become substantially more feasible and thus frequent over the past decade. However, relatively little is known regarding how these processes may be influenced by common naturalistic behaviors such as engaging in physical activity, which is thought to modulate the availability of neurometabolic resources. Here, we used an event‐related potential (ERP) approach to determine whether various intensities of aerobic exercise might affect the concurrent performance of attentional control mechanisms. Participants performed an additional‐singleton visual search task across three levels of aerobic activity while seated on a stationary bicycle: at rest, during moderate‐intensity exercise, and during vigorous‐intensity exercise. In addition to behavioral measures, attentional processing was assessed via lateralized ERPs referencing target selection (PCN) and distractor suppression (PD ) mechanisms. Whereas engaging in exercise resulted in speeded response times overall, moderate‐intensity exercise was found to uniquely eliminate the expression of distractor interference by the PCN while also giving rise to an unanticipated distractor‐elicited Ppc. These findings demonstrate workload‐specific and object‐selective influences of aerobic exercise on attentional processing, providing insights not only for approaching attention in real‐world contexts but also for understanding how attentional resources are used overall. Abstract : Although aerobic exercise is known to modulate cognitive performance, the neurocognitive origins of these effects remain unclear. By investigating ERP indices of attentional control during aerobic exercise, we provide evidence that cognitive performance may improve under specific cardiovascular workloads wherein supplemental neurometabolic resources are thought to become available. Additionally, our findings may suggest a resource‐based hierarchy between the top‐down mechanisms of attentional control.